2022
DOI: 10.22541/au.164268364.46044698/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Core bacteria associated with Cochlodinium polykrikoides(Dinophyta) blooms: diversity and function

Abstract: Harmful algal blooms (HABs) of Cochlodinium polykrikoides exert pressure on nutritional resources; however, little is known about how they affect bacterial diversity. To investigate this, 110 water samples were collected from the Southern Sea of South Korea. Samples were divided into three groups based on environmental factors and phytoplankton data with a similarity of 85% using non-metric multidimensional scaling. Group I represented high-severity blooms and had a mean C. polykrikoides abundance of 1,560 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…As a myosteatosis index, we used the NAMA/TAMA index, which was calculated by dividing NAMA by TAMA and multiplying the result by 100. 3 A higher NAMA/TAMA index value represents a higher degree of good-quality muscle. 15…”
Section: Evaluation Of Myosteatosismentioning
confidence: 99%
See 2 more Smart Citations
“…As a myosteatosis index, we used the NAMA/TAMA index, which was calculated by dividing NAMA by TAMA and multiplying the result by 100. 3 A higher NAMA/TAMA index value represents a higher degree of good-quality muscle. 15…”
Section: Evaluation Of Myosteatosismentioning
confidence: 99%
“…1 Our previous study demonstrated that myosteatosis was independently associated with systemic and hepatic insulin resistance, regardless of body size and the presence of other metabolic risk factors. 3 Computed tomography (CT) is commonly used to evaluate myosteatosis as a non-invasive alternative to muscle biopsy, providing reliable results that correlate with biopsy findings. 4,5 Given that CT density decreases with fatty tissue infiltration, the total abdominal muscular area (TAMA) in the CT axial image can be separated into three components based on CT density: normal-attenuation muscle area (NAMA), low-attenuation muscle area (LAMA), and inter-or intramuscular adipose tissue (IMAT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation